Optimizing Profits for ‘Meledak Food and Drink’ Restaurant Business in Tondano Using the Simplex Method - Indah Chairun Nisa; Anesty G. Hutajulu; Marcellina S Liu; Mikha Rajagukguk; Nopsi Kilaaku; Harly M Karamoy; Suci C Laode (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
The 'Food and Drink' restaurant is one of the Micro, Small, and Medium Enterprises (MSMEs) that is growing in Tondano. In the restaurant business, price issues and limited raw materials for production also affect sales which can cause profits to be less than optimal. This study was conducted with the aim of formulating a solution to the problem of optimizing profits in Micro, Small, and Medium Enterprises (MSMEs) from the 'Food and Drink' restaurant business. The simplex method is a way to solve linear programming problems where the repetition of mathematical procedures is carried out to test corner points until an optimal solution is found. The data used in this study is the data obtained from the results of interviews with the 'Food and Drink' restaurant business. Based on research through the simplex method linear programming, the results of the optimization calculation are that the 'Food and Drink' restaurant must increase the number of geprek chicken production by 1 portion and lalapan chicken by 12 portions per day. so that a maximum profit of Rp 2,652,000.00 is obtained.